NILAI EDUKASI TAMAN KOTA DI SIDOARJO - J. Priyanto Widodo (Universitas Negeri Malang, 2020)
Sidoarjo is an important city in East Java and it has several city parks with unique features and values. This article aims to elaborate the educational values of a city park in Sidoarjo. The data were collected trough review of literature and observation. Among several city parks in Sidoarjo, this article focus on the Alun-alun (city square) with Jayandaru Monument as its unique feature. The finding suggested that the city park in Sidoarjo has several educational values: (1) cultural values, (2) identity value, (3) sense of pride, (4) love to the city, (5) diversity and (6) tolerance.